The Italians in the Time of Coronavirus: Psychosocial Aspects of the Unexpected COVID-19 Pandemic - Favieri, Francesca; Forte, Giuseppe; Tambelli, Renata; Casagrande, Maria (Frontiers in Psychiatry, 2021)
Background The COVID-19 pandemic is a worldwide public health emergency that forced the Italian Government to deliberate unprecedented actions, including quarantine, with a relevant impact on the population. The present study is one of the first Italian nationwide survey within the first period of the COVID-19 outbreak aimed to understand the social and psychological impact of the COVID-19 outbreak. Methods An online survey collected information on socio-demographic data, history of direct or indirect contact with COVID-19, and other information concerning the COVID-19 emergency. The General Psychological Well-Being Index and a modified version of the PTSD Checklist for DSM-5 focused on the COVID-19 experience assessed the respondents’ general psychological condition. Results Of 1639 respondents equally distributed in the Italian territory, 5.1% reported PTSD symptomatology, and 48.2% evidenced lower psychological well-being linked to COVID-19 diffusion. Lower psychological well-being was significantly higher in women, younger than 50 years, and with health risk factors. Lower psychological well-being was also detected in individuals who did not know if they were infected, who have had direct exposure or were uncertain about their exposure to COVID-19, or who knew infected people. Regarding the social and behavioral consequences, respondents perceived worsening in demographic, economic, social, and relational conditions. Moreover, they reported increased film viewing, cookhouse time, social media use, and decreased physical activity. Conclusion COVID-19 pandemic appears to be a risk factor for psychological diseases in the Italian population, as previously reported in the Chinese people. About half of the respondents reported a significant psychological impact. Moreover, we confirmed the role of restraining measures that led to modify lifestyles, social perception, and confidence in the institutions. These results underline the need for further studies aimed to develop psychological interventions to minimize the consequences of the COVID-19 pandemic.